2019
DOI: 10.1016/j.aott.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented recurrence of carpal tunnel syndrome by metaplastic synovial cyst in the carpal tunnel

Abstract: Metaplastic synovial cyst (MSC) is a benign cystic lesion observed after surgical intervention and recurrent skin trauma. Because of its rarity, the etiology is not fully understood. The most emphasized etiologic factors are recurrent surgical procedures and cutaneous pathologies, which cause cutaneous fragility and abnormal wound formation. In the literature, MSC is exemplified as a mass that can be observed by the naked eye and palpated. All patients had a history of previous surgical procedures in the area.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, when this is not the case, it can be difficult to diagnose. A case of a metaplastic synovial cyst in the carpal tunnel highlights this as they did not perform ultrasound or MRI preoperatively to aid their diagnosis [14]. Lipomas have also been reported to cause other forms of entrapment neuropathy in both upper and lower limbs [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, when this is not the case, it can be difficult to diagnose. A case of a metaplastic synovial cyst in the carpal tunnel highlights this as they did not perform ultrasound or MRI preoperatively to aid their diagnosis [14]. Lipomas have also been reported to cause other forms of entrapment neuropathy in both upper and lower limbs [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review of CMSC cases performed by Fukuyama et al, 3 distribution of reported cases according to body site varied; however, limbs were found to be the most commonly involved area. A PubMed search of articles indexed for MEDLINE as well as a Google Scholar search using the term cutaneous metaplastic synovial cyst revealed at least 37 cases reported in the English-language literature, [3][4][5][6][7][8][9] including our present case. The pathogenesis remains uncertain; however, a majority of previously reported cases of CMSC characteristically have been associated with a pre-existing lesion, with most presentations developing at surgical scar sites secondary to operation or trauma.…”
Section: What's Your Diagnosis?mentioning
confidence: 99%